C-E (curtailment – Energy share) map: An objective and quantitative measure to evaluate wind and solar curtailment. (May 2022) - Yasuda, Yoh; Bird, Lori; Carlini, Enrico Maria; Eriksen, Peter Børre; Estanqueiro, Ana; Flynn, Damian; Fraile, Daniel; Gómez Lázaro, Emilio; Martín-Martínez, Sergio; Hayashi, Daisuke; Holttinen, Hannele; Lew, Debra; et al.
Abstract: As the share of VRE (variable renewable energy) has grown rapidly, curtailment issues have arisen worldwide. This paper evaluates and compares curtailment situations in selected countries using an objective and quantitative evaluation tool named the " C-E map " (curtailment-energy share map). The C-E map is a correlation map between curtailment ratios that mean curtailed wind (or solar) energy per available energy and energy shares of wind (or solar). The C-E map can draw a historical trend curve in a given country/area, as an at-a-glance tool to enable historical and/or international comparison. The C-E map also can classify the given countries/areas into several categories, according to the current levels of curtailment ratio and historical trends. The C-E map helps institutional and objective understanding of curtailment for non-experts including policy makers. Highlights: Curtailment is one of the most important issues for wind and solar integration. Global curtailment data in Europe, North America, China and Japan was evaluated. Curtailment ratio does not always increase as wind and solar share increases. Some countries/areas decreased curtailment ratio by enhancing of flexibility resource. C-E (Curtailment - Energy Share) Map can help to grab historical trend of curtailment.